SMARCA4 mutations in KRAS‐mutant lung adenocarcinoma: a multi‐cohort analysis. Issue 2 (17th December 2020) - Liu, Liang; Ahmed, Tamjeed; Petty, William J.; Grant, Stefan; Ruiz, Jimmy; Lycan, Thomas W.; Topaloglu, Umit; Chou, Ping‐Chieh; Miller, Lance D.; Hawkins, Gregory A.; Alexander‐Miller, Martha A.; O'Neill, Stacey S.; et al.
Abstract : KRAS is a key oncogenic driver in lung adenocarcinoma (LUAD). Chromatin‐remodeling gene SMARCA4 is comutated with KRAS in LUAD; however, the impact of SMARCA4 mutations on clinical outcome has not been adequately established. This study sought to shed light on the clinical significance of SMARCA4 mutations in LUAD. The association of SMARCA4 mutations with survival outcomes was interrogated in four independent cohorts totaling 564 patients: KRAS ‐mutant patients with LUAD who received nonimmunotherapy treatment from (a) The Cancer Genome Atlas (TCGA) and (b) the MSK‐IMPACT Clinical Sequencing (MSK‐CT) cohorts; and KRAS ‐mutant patients with LUAD who received immune checkpoint inhibitor‐based immunotherapy treatment from (c) the MSK‐IMPACT (MSK‐IO) and (d) the Wake Forest Baptist Comprehensive Cancer Center (WFBCCC) immunotherapy cohorts. Of the patients receiving nonimmunotherapy treatment, in the TCGA cohort ( n = 155), KRAS ‐mutant patients harboring SMARCA4 mutations (KS) showed poorer clinical outcome [ P = 6e‐04 for disease‐free survival (DFS) and 0.031 for overall survival (OS), respectively], compared to KRAS ‐ TP53 comutant (KP) and KRAS ‐only mutant (K) patients; in the MSK‐CT cohort ( n = 314), KS patients also exhibited shorter OS than KP ( P = 0.03) or K ( P = 0.022) patients. Of patients receiving immunotherapy, KS patients consistently exhibited the shortest progression‐free survival (PFS; P = 0.0091) in the MSK‐IO ( n = 77), and the shortest PFS ( P = 0.0026) and OS ( P = 0.0014) in the WFBCCC ( n = 18) cohorts, respectively. Therefore, mutations of SMARCA4 represent a genetic factor leading to adverse clinical outcome in lung adenocarcinoma treated by either nonimmunotherapy or immunotherapy. Abstract : In this work, we study the survival outcomes of patients with lung adenocarcinoma in four independent cohorts. By classifying patients with KRAS mutations into three subgroups based on their mutation status of TP53 and SMARCA4, our analysis indicates that patients harboring both KRAS and SMARCA4 mutations do not benefit from the treatment with nonimmunotherapy or immune checkpoint inhibitor‐based immunotherapy. Alternative treatment strategy is requested for this subset of patients.